2020
DOI: 10.1002/hyp.13659
|View full text |Cite
|
Sign up to set email alerts
|

Establishing irrigation potential of a hillside aquifer in the African highlands

Abstract: Feeding 9 billion people in 2050 will require sustainable development of all water resources, both surface and subsurface. Yet, little is known about the irrigation potential of hillside shallow aquifers in many highland settings in sub-Saharan Africa that are being considered for providing irrigation water during the dry monsoon phase for smallholder farmers. Information on the shallow groundwater being available in space and time on sloping lands might aid in increasing food production in the dry monsoon pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…However, from the field observation during harvest, the maximum rooting depths for onion, garlic, cabbage, and pepper are less than 60 cm. On the other hand, the depth of groundwater level varies spatially and temporarily; in the dry season 4-15 m in Dangishta and 8-20 m in Robit was observed [52]. Gao et al [53] explained that the upward capillary rise is negligible when the groundwater depth is more than 2.5 m.…”
Section: Crop Coefficientsmentioning
confidence: 99%
“…However, from the field observation during harvest, the maximum rooting depths for onion, garlic, cabbage, and pepper are less than 60 cm. On the other hand, the depth of groundwater level varies spatially and temporarily; in the dry season 4-15 m in Dangishta and 8-20 m in Robit was observed [52]. Gao et al [53] explained that the upward capillary rise is negligible when the groundwater depth is more than 2.5 m.…”
Section: Crop Coefficientsmentioning
confidence: 99%
“…Performing the annual water budget with the data in Table 3 assuming that evapotranspiration between June and September is 416 mm [67], the excess rainfall that cannot be accounted for is 465 mm in 2015, 492 mm in 2016, and 547 mm in 2017. Some of the water which is unaccounted for would have evaporated during the dry phase, but according to observations in other watersheds within 100 km from the study area, this would constitute less than 200 mm a −1 [16,92]. Field evidence ( Figure 6a) suggests that the remainder of the unaccounted water flowed out of the watershed via the subsurface through the faults and lineaments.…”
Section: Interaction Of Geology and Hydrologymentioning
confidence: 71%
“…The water levels in the piezometers in the Gomit watershed were nearly independent of rainfall once they reached their maximum levels ( Figure 7). In other watersheds like Debre Mawi, the water table fluctuated with the amount of rainfall [13,16,58]. In addition, Alemie et al [13] observed for a few hand-dug wells that the groundwater level remained constant during the wet phase.…”
Section: Relationship Between Geology and Perched Groundwatermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to surface runoff, interflow is a major component of the discharge at the watershed outlet in humid highlands (Gurtz et al, 2003;Jackson et al, 2014;Setegn et al, 2010;Whipkey, 1965). Interflow occurs when the soil at the hillside is above field capacity and a saturated layer develops above the hardpan (Alemie et al, 2019;Tilahun et al, 2014Tilahun et al, , 2019. The water table depth above the hardpan increases from the divide to the saturated area (Bayabil et al, 2010;Betson, 1964;Guzman et al, 2017a, b).…”
Section: Introductionmentioning
confidence: 99%